SUBSTANTIVE (CONTENT-RELATED) CHARACTERISTICS OF DEVIANT BEHAVIOR AS A SOCIAL AND PSYCHOLOGICAL PHENOMENON - Burxonova Dilnoza Soyibovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article is devoted to an important social problem of modern society - deviant behavior in the system of social relations. The article discusses the results of a theoretical analysis of deviant behavior. An overview of the development of this concept is given from ancient times to the present day. Conclusions were made on the substantive features of deviant behavior as a socio-psychological phenomenon. The materials of the article are of practical importance for psychologists, social workers and employees of educational institutions.